Analisis Pengaruh Stock Split Terhadap Volume Perdagangan Dan Return Saham yang Terdaftar di Bursa Efek Indonesia pada Tahun 2011-2015 - Masdupi, Erni; Megawati, Megawati; Irawan, Rio (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2017)
This reseach aims to determine the effect of the stock split analysis of the trading volume and stock returns. This study using a quantitative research design causal. In this study population is all companies doing stock split at the company, which is listed in the Indonesia Stock Exchange (IDX) on 2011-2015, whose number is not known and the sample totaling 22 companies. Data were collected by using documentation. Data analyzed using paired sample t-test. The results of this study indicate that (1) there was no change in the volume of stock trading before and after the stock split and (2) there was no difference in stock returns before and after the stock split on the company stock split in the Indonesia Stock Exchange (BEI) 2011-2015.